2009
DOI: 10.1002/14651858.cd001199.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant and adjuvant therapy for surgical resection of hepatocellular carcinoma

Abstract: Does quality of reports of randomised trials a ect estimates of intervention e icacy reported in meta-analyses?. Lancet 1998;352:609-13. Nagourney 1987 Nagourney DM, Adson M. Major hepatic resections for hepatoma in the West. In: Wanebo HJ editor(s). Hepatic and Biliary Cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 30 publications
1
80
2
5
Order By: Relevance
“…Although all but one case with gross vascular invasion suspected recurrence after HCC resection is important because there is currently no effective adjuvant or neoadjuvant therapy (30). In this regard, we believe that our results demonstrated that a prediction model that uses preoperative MR imaging has the potential to preoperatively identify high-risk patients, for whom other treatment modalities such as liver transplantation or a wider extent of resection can be considered.…”
Section: Discussionmentioning
confidence: 63%
“…Although all but one case with gross vascular invasion suspected recurrence after HCC resection is important because there is currently no effective adjuvant or neoadjuvant therapy (30). In this regard, we believe that our results demonstrated that a prediction model that uses preoperative MR imaging has the potential to preoperatively identify high-risk patients, for whom other treatment modalities such as liver transplantation or a wider extent of resection can be considered.…”
Section: Discussionmentioning
confidence: 63%
“…Currently, the conclusive role of adjuvant therapy following curative resection of HCC remains to be defined (Samuel et al 2009). Nevertheless, several adjuvant strategies have been tested in clinical trials, including systemic and intra-arterial chemotherapy, intraarterial radiolabeled lipiodol, TACE, acyclic retinoids, interferon, adoptive immunotherapy, autologous tumor vaccine, and, more recently, sorafenib (Xie et al 2012;Furtado et al 2014).…”
Section: Adjuvant Therapy After Surgical Resectionmentioning
confidence: 99%
“…3 Limited adjuvant therapies are available for advanced HCC patients. 4,5 Sorafenib, a Raf-1 kinase inhibitor, was reported to extend patient survival for nearly 3 months. 6 However, a recent multicenter, double-blinded trial concluded that sorafenib did not extend recurrence-free survival, but increased adverse effects of the treatment, 3 and the findings are consistent with a growing list of negative reports from primary or adjuvant use after resection, ablation, or transarterial chemoembolization.…”
mentioning
confidence: 99%